Empathy at the Heart of Darkness: Empathy Deficits That Bind the Dark Triad and Those That Mediate Indirect Relational Aggression - Heym, Nadja; Firth, Jennifer; Kibowski, Fraenze; Sumich, Alexander; Egan, Vincent; Bloxsom, Claire A. J. (Frontiers in Psychiatry, 2019)
The dark triad (DT) traits - psychopathy, narcissism and Machiavellianism - have collectively been linked to reduced empathy and increased aggression; however, their association with distinct empathic subtypes remains unclear; and unique links to indirect relational aggression (IRA) have not been delineated. Moreover, whether dark traits should be conceptualised individually, as a dyad or as a triad with a dark core centred around the absence of empathy is debated. The current study examines (i) whether impaired empathy indeed represents a common ‘dark core’ binding Machiavellianism, narcissism, and psychopathy, and (ii) this core explains associations between the dark traits and IRA. Participants (N=301, 262F/39M) completed measures of the DT traits, cognitive and affective empathy components and IRA (Social Exclusion, Malicious Humour and Guilt Induction). The individual traits model without links between narcissism and IRA showed the best fit, suggesting that, at least in the context of IRA, the DT traits are best viewed as three independent personality traits. Distinct cognitive and affective empathy deficits and capacities are seen in the DT. Peripheral responsivity was the only type of empathy deficit associated with all dark traits, but unrelated to IRA. Psychopathy was the strongest indicator of impaired empathy and all IRAs; however, only online simulation, an affect-related cognitive empathy facet, partially mediated the relationships of psychopathy and Machiavellianism with IRA. Whilst the unique pathways for the dark trait traits suggest stronger alignment of psychopathy and Machiavellianism in their empathic deficits and indirect aggression; the data do not support the notion that an unempathic dark core underpinning all three traits drives indirect aggression. This is the first paper delineating the specific empathic deficits involved using a facet approach and their link to indirect forms of aggression, and as such further inform theoretical models of aggression in the DT, and offer some clarity on the debates surrounding the unempathic dark core in the DT.